Placebo and nocebo responses in painful diabetic neuropathy: systematic review and meta-analysis - Frisaldi, Elisa; Vollert, Jan; Al Sultani, Husam; Benedetti, Fabrizio; Shaibani, Aziz (Pain, 2024)
This preregistered (CRD42021223379) systematic review and meta-analysis aimed to characterize the placebo and nocebo responses in placebo-controlled randomized clinical trials (RCTs) on painful diabetic neuropathy (PDN), updating the previous literature by a decade. Four databases were searched for PDN trials published in the past 20 years, testing oral medications, adopting a parallel-group design. Magnitude of placebo or nocebo responses, Cochrane risk of bias, heterogeneity, and moderators were evaluated. Searches identified 21 studies (2425 placebo-treated patients). The overall mean pooled placebo response was −1.54 change in the pain intensity from baseline [95% confidence interval (CI): −1.52, −1.56, I2 = 72], with a moderate effect size (Cohen d = 0.72). The pooled placebo 50% response rate was 25% [95% CI: 22, 29, I2 = 50%]. The overall percentage of patients with adverse events (AEs) in the placebo arms was 53.3% [95% CI: 50.9, 55.7], with 5.1% [95% CI: 4.2, 6] of patients dropping out due to AEs. The year of study initiation was the only significant moderator of placebo response (regression coefficient = −0.06, [95% CI: −0.10, −0.02, P = 0.007]). More recent RCTs tended to be longer, bigger, and to include older patients (N = 21, rs = 0.455, P = 0.038, rs = 0.600, P = 0.004, rs = 0.472, P = 0.031, respectively). Our findings confirm the magnitude of placebo and nocebo responses, identify the year of study initiation as the only significant moderator of placebo response, draw attention to contextual factors such as confidence in PDN treatments, patients' previous negative experiences, intervention duration, and information provided to patients before enrollment.